Improved measurement of the absolute branching fraction of D+ -> (K)over-bar(0)mu(+)nu(mu) - Çetin, Serkant Ali (Springer, 2016)
Abstract By analyzing 2.93 fb(-1) of data collected at root s = 3.773 GeV with the BESIII detector, we measure the absolute branching fraction B(D+ -> (K) over bar (0) (+)(mu)nu(mu)) = (8.72 +/- 0.07(stat). +/- 0.18(sys).) %, which is consistent with previous measurements within uncertainties but with significantly improved precision. Combining the Particle Data Group values of B(D-0 -> K- mu(+)nu(mu)), B(D+-> (K) over bar (0)e(+)nu(e)), and the lifetimes of the D-0 and D+ mesons with the value of B(D+ -> (K) over bar (0)mu(+)nu(mu)) measured in this work, we determine the following ratios of partial widths: Gamma (D-0 -> (K) over bar (-)mu(+)nu(mu))/Gamma (D+ -> (K) over bar (0)mu+nu(mu)) = 0.963 +/- 0.044 and Gamma (D+ -> (K) over bar (0) mu+nu(mu))/Gamma(D+ -> (K) over bar (0)e+nu(e)) = 0.988 +/- 0.033.
Keywords: MONTE-CARLO; DECAYS; E(+)E(-); HEAVY